Contact ureterolithotripsy of a giant ureteral stone in a 3-year-old child - I. V. Klyuka; V. V. Sizonov; I. I. Belousov; V. V. Vigera (Вестник урологии, 2023)
Giant ureteral stones in young children are extremely rare and their surgical treatment tactics are variable. The present case describes a case of effective and safe endoscopic treatment of giant ureteral stones in a young child. The patient is a 3-year-old male child. Examination findings of abdominal pain and fever verified a left distal ureteric stone up to 30 mm complicated by ureterohydronephrosis. The first treatment stage was ureteral stenting, in which the stone migrated to the middle ureteral third. The second treatment stage was contact ureterolithotripsy with a 9 Ch semi-rigid ureteroscope («Richard Wolf» GmbH, Knittlingen, Germany) and Swiss LithoClast® 2 pneumatic lithotripter («E.M.S. Electro Medical Systems» S.A., Nyon, Suisse), ureteral stenting (2-way PigTail, 4.5 Ch). The third treatment stage in the delayed period was extracorporeal shockwave lithotripsy of the steinstrasse using the Dornier Compact Sigma («Dornier MedTech» GmbH, Weßling, Germany) and stent removal. Residual stones were not revealed according to the follow-up examination. No treatment complications were registered. The multimodal staged treatment of a giant ureteral stone resulted in its complete elimination. Next-step ureteral endoscopy made it possible to identify concomitant pathology of the proximal ureter, which required its evaluation in the delayed period. Ureteral stenting contributed to the restoration of renal function. The result achieved reflects the maximum efficiency and high safety of the surgical technique applied.